Micro Nutrient Content and Growth of Oil Palm (Elaeis guineensis Jacq) Applied to Oil Palm Liquid Waste Using the Biopori Method - Rai Edgar Gusti; Nelvia Nelvia; Anthony Hamzah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The area of ​​oil palm plantations in Indonesia continues to increase, along with that, Palm oil mill also increases. Each Palm oil mill produces liquid waste (LWPOF) in large numbers that can be utilized. The aim of this research was to study the main effect of LWPOF application and the number of biopores and their interactions on micro nutrient content and oil palm growth. The research was conducted in oil palm plantations at the Faculty of Agriculture, Riau University from June to December 2019 in the form of experiments arranged according to a completely randomized factorial design. The first factor is the LWPOF dose which consists of 3 levels (7,5 liters, 10 liters, and 12,5 liters) and the second factor is the amount of biopores consisting of 3 levels (2, 4, and 6), repeated 3 times and there were 3 experimental plants, so that 81 units of experimental plants were obtained. The parameters observed consisted of leaf micro nutrient content, plant height increase, number of fronds, midrib width, and thickness of oil palm fronds. From the experiment, known that 7,5 liters plant increases the nutrient content of copper, and the LWPOF dose of 12,5 liters increases the height, number, width and thickness of oil palm fronds, while the number of biopores 2 and 6 increases leaf manganese nutrient content. 7,5 liters of planting followed by the number of biopores in 6 biopores increases the nutrient content of manganese in the leaves and the number of midribs of oil palm plants.